The borrowed words in the modern dictionary of pop culture (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article deals with the borrowings, which  name the phenomena of a masscult; common paradigmatic and syntagmatic  laws for common languages are found out; the expansion of dictionary structure common literature language is certified.
Keywords: the borrowed word; pop culture; word formation system; functioning